Selective reactions to different killer whale call categories in two delphinid species - Bowers, Matthew T.; Friedlaender, Ari S.; Janik, Vincent M.; Nowacek, Douglas P.; Quick, Nicola J.; Southall, Brandon L.; Read, Andrew J. (Journal of Experimental Biology, 2018)
The risk of predation is often invoked as an important factor influencing the evolution of social organization in cetaceans, but little direct information is available about how these aquatic mammals respond to predators or other perceived threats. We used controlled playback experiments to examine the behavioral responses of short-finned pilot whales ( Globicephala macrorhynchus ) off Cape Hatteras, NC, USA, and Risso's dolphins ( Grampus griseus ) off the coast of Southern California, USA, to the calls of a potential predator, mammal-eating killer whales. We transmitted calls of mammal-eating killer whales, conspecifics and baleen whales to 10 pilot whales and four Risso's dolphins equipped with multi-sensor archival acoustic recording tags (DTAGs). Only playbacks of killer whale calls resulted in significant changes in tagged animal heading. The strong responses observed in both species occurred only following exposure to a subset of killer whale calls, all of which contained multiple non-linear properties. This finding suggests that these structural features of killer whale calls convey information about predatory risk to pilot whales and Risso's dolphins. The observed responses differed between the two species; pilot whales approached the sound source while Risso's dolphins fled following playbacks. These divergent responses likely reflect differences in anti-predator response mediated by the social structure of the two species.